Polyphyllin VI screened from Chonglou by cell membrane immobilized chromatography relieves inflammatory pain by inhibiting inflammation and normalizing the expression of P2X3 purinoceptor - Luo, Zhenhui; Wang, Tingting; Zhang, Zhenglang; Zeng, Hekun; Yi, Mengqin; Li, Peiyang; Pan, Jiaqin; Zhu, Chunyan; Lin, Na; Liang, Shangdong; Verkhratsky, Alexei; Nie, Hong (Frontiers in Pharmacology, 2023)
Objective: Inflammatory pain is one of the most common diseases in daily life and clinic. In this work, we looked into the bioactive components of the traditional Chinese medicine Chonglou and studied their analgesic effects and mechanisms of action. Material and methods: Molecular docking technology and U373 cells overexpressing P2X3 receptors combined with the cell membrane immobilized chromatography were used to screen possible CL bioactive chemicals that influenced and regulated the P2X3 receptor. Moreover, we investigated the analgesic and anti-inflammatory effects of Polyphyllin VI, in mice with chronic neuroinflammatory pain induced by CFA (complete Freund’s adjuvant). Results: The results of Cell membrane immobilized chromatography and molecular docking showed that PPVI was one of the effective compounds of Chonglou. In mice with CFA-induced chronic neuroinflammatory pain, PPVI decreased the thermal paw withdrawal latency and mechanical paw withdrawal threshold and diminished foot edema. Additionally, in mice with CFA-induced chronic neuroinflammatory pain, Polyphyllin VI reduced the expression of the pro-inflammatory factors IL-1, IL-6, TNF-, and downregulated the expression of P2X3 receptors in the dorsal root ganglion and spinal cord. Conclusion: Our work identifies PPVI as a potential analgesic component in the Chonglou extract and PPVI reduces pain by inhibiting inflammation and normalizing P2X3 receptor expression in the dorsal root ganglion and spinal cord.